Research effects of Testosterone undecanoate administration on metabolic and hormonal parameters at men with an obesity and a chronic heart failure - N. P. Goncharov; G. V. Katsya; L. M. Gaivoronskaya; V. I. Zoloedov; V. M. Uskov (Андрология и генитальная хирургия, 2014)
The ATP III criteria of the metabolic syndrome (MS) comprise impaired fasting glucose (> 5.6 nmol/L), waist circumference > 102 cm, hypertension (> 130/85 mm Hg), high triglycerides (> 1.7 nmol/L) and low HDL-cholesterol (≤1.03 nmol/L). Aldosterone is currently recognized as a key factor in pathogenesis of cardiovascular diseases and insulin resistance, linking hypertension to MS and obesity. Those results prompted us to study the effects of testosterone administration on metabolic and hormonal parameters, including the effects on serum aldosterone on men with MS, lower-than-normal serum testosterone and chronic heart failure. Patients were included in research is older than 40 years.The study group received two injections with Testosterone undecanoate (1000 mg) with three month interval. After 24 weeks of testosterone treatment, there were significant declines of insulin and homeostatic model assessment and of serum aldosterone (but no changes in blood pressure). Serum glucose declined but not significantly. There was a slight increase in LDL-cholesterol and a decrease in triglycerides. Other variables of MS and other biochemical variables did not change. Echocardiographical variables did not change. The AMS showed improvements over the first 3 months after testosterone administration but, while sustained, there was no further improvement. Thus, short-term introduction of Testosterone undecanoate within 24 weeks leads to improvement of some markers of MS, but the most expressed and low-studied effect is inhibitory action of testosterone on the increased concentration of aldosterone in serum.